PERSEPSI MASYARAKAT TERKAIT POTENSI PENERAPAN PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) DI PROVINSI KALIMANTAN SELATAN (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2020)
The Covid-19 virus appeared at the end of 2019 which was first discovered in Wuhan, China. This virus is widespread in 2020 throughout the world, including Indonesia. South Kalimantan Province cannot be separated from the spread of this virus due to high population mobility, so PSBB is needed with the aim of inhibiting the spread of the virus. Analysis of the potential for implementing PSBB in South Kalimantan Province is needed to determine the level of success that has been implemented. The research objective was to analyze public perceptions regarding the implementation of PSBB in South Kalimantan Province. The research method used quantitative descriptive which was carried out through the online questionnaire Survey123, conducted on July 21, 2020 to August 10, 2020. Based on the research results, the majority of the people of South Kalimantan Province agreed with the existence of the PSBB, but the level of community compliance with government recommendations was still low. The solutions that can be provided include forming an epidemiological team, testing or evaluating the implementation of the PSBB on social and economic aspects, and the need for socialization to the public regarding the importance of government recommendations regarding policies to stop the spread of Covid-19.